Policy-based population projections for the European Union: A complementary approach - Philip Cafaro; Patrícia Dérer (Comparative Population Studies (CPoS), 2019)
We present new population projections out to 2100 for the countries of the European Union and for the EU as a whole under a wide range of fertility and migration scenarios. As policy-based projections rather than forecasts, they aspire not to maximize predictive success regarding future demographic developments, but to accurately show the impact of different migration and socio-economic policy choices on population numbers. Our chief aim is to clarify those policy choices for European citizens and policymakers. We show that demographic policies have the potential to markedly increase or decrease future populations across the EU. Migration policy offers greater scope for infl uencing future population numbers than policies aimed at infl uencing national fertility rates. In countries with particularly low fertility rates or high emigration levels, egalitarian economic and family support policies have the potential to limit future population decreases to a signifi cant extent, especially in combination. In most cases, EU nations are well placed to stabilize or slowly reduce their populations by continuing status quo policies or with moderate changes. Thus they are well placed to achieve one of the necessary conditions for creating ecologically sustainable societies.
urn:nbn:de:bib-cpos-2019-14en1
Keywords: 300; Population projections; European Union; Fertility; Migration; Population policy